Foster Carers’ Perspectives about Contact in Portugal and Spain. - Delgado, Paulo; Bernedo-Muñoz, Isabel María; Carvalho, João M. S.; Salas-Martínez, María Dolores; García-Martín, Miguel Ángel (Redfame Publishing, 2019)
This study aims at comparing the nature and processes of contact between children in foster care and their birth families; the relationship between the existence and quality of contact and foster carers’ burden; and the relationship between the existence or not of contact and the existence of reunification plans. Following a quantitative approach, data have been collected in Portugal and Spain from foster carers and professionals using questionnaires and Zarit's Carer scale. The results show that the existence of contact is not related to carers’ burden or stress, but there is an association between contact and reunification plans. As a consequence, several implications to practice are presented.
Keywords: Acogimiento familar; Reunification